Từng bước nói tiếng Anh lưu loát. Tập 3 - Allen, Christopher B. (Tổng hợp TP.HCM, 2011)
Part 1: Family Relationships Act 2 Scene 3 Scene 5 Act 3: Let's Review Act 4: Let's Practice Part 2: Routines and Habits Act 2 Scene 3 Scene 5 Act 3: Let's Review Act 4: Let's Practice The Summary